Perceived Research Misconduct Among the Pharmacy Academics and Students: A Cross-Sectional Survey Study in Malaysia - Ng, Wan Ping; Pang, Khong Yun; Ooi, Pei Boon *; Phan, Chia Wei (Springer, 2023)
In this study, the levels of knowledge, awareness, and acceptance of research misconduct were investigated among the Pharmacy academics and students in Malaysia. A cross-sectional study using an online questionnaire was carried out. A total of 393 pharmacy academics and students in Malaysia were involved. Perceived research misconduct, as defined in this study as the perception of any research misconduct performed or observed by the respondents at their institution, was captured and further analyzed. The data was analysed using PLS-SEM to assess the hypotheses which were formulated prior to the survey. The findings show that there is a statistically significant positive relationship between the awareness of terminologies regarding research misconduct and perceived research misconduct in the workplace of respondents. However, the acceptance of unethical practices in research demonstrates a negative correlation with perceived research misconduct. Knowledge and awareness regarding research misconduct have no statistically significant relationship with perceived research misconduct in this study. Both awareness of terminologies and acceptance of unethical practices explained a 10.8% variance in perceived research misconduct. Therefore, our study indicates that the awareness, knowledge, and acceptance of research misconduct might not be the main predictors of questionable conduct of research among pharmacy academics and students. Future study on the relationship between other factors which might contribute to research misconduct is highly recommended to investigate the significant contributing factors of irresponsible conduct of research among the Pharmacy academics and students in Malaysia.